(untitled) (Indian Journal of Chemistry (IJC), 2026)
Ru(II) polypyridyl complexes of [Ru(A)2NPPIP] (ClO4)2.2H2O, where NPPIP = 2-(4-(pyrimidine-5-yl)phenyl)-1H-imidazo[4,5-f][1,10]phenanthroline and A = phen = (1,10-phenanthroline)(1), bpy = bipyridyl(2) & dmb = 4,4’-dimethyl-2,2’-bipyridine(3), have been synthesized and characterized using various spectroscopic techniques. The interaction of these complexes with DNA was studied using biophysical methods, including absorption, emission, and viscosity measurements. The results indicate that the Ru(II) polypyridyl complex binds to DNA primarily through intercalation. Among the complexes, the phen complex exhibits the strongest DNA binding affinity, followed by bpy and dmb, highlighting the influence of the ancillary ligand on DNA binding specificity. This was further confirmed by the binding constants (Kb), which were determined to be 2.5X10⁵ M-1(from UV-Vis absorption) and 7.2X10⁶ M-1(from fluorescence emission studies), and the Stern-Volmer quenching constant (Ksv), which was 9.2X10³. Antimicrobial studies on Gram-negative (E. coli and K. pneumoniae) and Gram-positive (S. aureus and E. faecalis) bacteria showed significant activity. Additionally, the anti-cancer potential of the complexes was evaluated using the MTT assay against the MCF-7 cell line, demonstrating strong anticancer activity correlated with their DNA binding properties.